Perancangan Proses Bisnis Sekolah Musik Dengan Menggunakan Business Process Model And Notation - Kanggep Andrijana Kusuma; Angga Prama Agusmar Yahya; Alman Naufal; Shanti Maulani; Deassy Ratna Juwita Sari (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2026)
This study aims to analyze the business processes that occur in music schools to improve operational effectiveness and efficiency. The research method used is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the music school business process consists of seveal main stages, namely student registration, class scheduling, learning processes, payments, and evaluation. Business process modeling was carried out using Business Process Model and Notation (BPMN) to systematically visualize the workflow. Based on the analysis conducted, several obstacles were found such as a manual recording system, potential schedule conflicts, and a suboptimal payment system. Therefore, it is recommended to implement an integrated information system to improve service quality and operational efficiency of music schools.